Collaborative and Energy-Efficient Speech Monitoring on Smart Devices. - Leppanen, Jarno; Pelkonen, Mikko; Guo, Haipeng; Hemminki, Samuli; Nurmi, Petteri; Tarkoma, Sasu (Computer (00189162), 2016)
The Collaborative Energy-Efficient Speech Recognition (CeeSR) platform enables speech monitoring in everyday situations by opportunistically connecting smart devices and capturing and unifying their audio streams. An audio-source selection algorithm balances energy cost with information usefulness, and another algorithm automatically detects when devices should share data.